Descriptive Study about Organizing Strategy of Learning in the Improvement Sub Theme Based on Local Potencies at Gugus Parkit Subdistrict Ungaran Barat - Risky, Bella Herkiana; Waluyo, Edi (Jurusan PGPAUD FIP UNNES, 2017)
Learning that is in compliance with the environmental conditions of the child will bewell received. The cluster became one of the efforts in achieving the educational keberrasilan. The cluster is a cluster of parakeet which was in the tourist area of realmsand has the local resources. The goal of this research is to know the organizing strategy of learning in the development of the sub theme-based potential of the local cluster of parakeets and a supportive factor in the process of organizing it. The methods used in this research is a descriptive study of qualitative data collection techniques namely observation, documentation and interviews. Data analysis technique used is a triangulation source. Informants in this study is the Chairman of the cluster and the cluster members informant eight Parakeets. The results of this research were obtained that there were seven steps of elaboration undertaken in organizing the learning strategy. The step was the presentation of the contents of the framework up to the stage of granting summary. Development of sub theme was performed on the stage of elaboration of coverage. Consider the learning capacity of the well. The development of the theme of learning that is conducted in accordance with the principle of the development of the theme of learning that is close to children, simple, attractive and isidental. The resulting conclusions in this study is a strategy of organizing learning in the development of the sub theme-based local potential cluster parakeets do the stages ofelaboration as well. Factors that support is the environment around the cluster of parakeets can be a learning resource that is good because it has the potential of various local aspects. The second factor that teachers know the principle of developing the theme of learning. Keywords: Learning, development of Organizing Strategy Sub Theme-based learning Potential, local Cluster.